Effects of spacing techniques on EFL learners’ recognition and production of lexical collocations - Farvardin, Mohammad Taghi (Universitas Pendidikan Indonesia, 2019)
Spacing technique is a kind of strategy whereby the vocabulary will be revised with breaks between the revision sessions. Using spacing techniques in foreign and second language learning has received a lot of attention recently. However, there are many questions about how EFL learners are able to learn and remember target words. Moreover, few studies have thus far been carried out on the effect of using spacing techniques on EFL learners’ lexical collocational knowledge. Thus, this study probed the effects of spacing techniques on EFL learners’ recognition and production of lexical collocations. To this end, 62 EFL learners at a junior high school were selected from three intact classes. Each class was assigned to one experimental condition, i.e. uniform spaced retrieval (USR), expanded spaced retrieval (ESR), and massed retrieval (MR). Twelve collocations unknown to the participants were selected as the target collocations. The treatment lasted for one session for the MR group (80 minutes) and four sessions for the USR and ESR groups (each session 20 minutes). After the last treatment session, a multiple-choice test and a translation test were administered to measure the participants’ recognition and production of the target collocations, respectively. Two delayed posttests were also administered two weeks and four weeks after the last treatment session. The results revealed that both ESR and USR groups significantly outperformed the MR group on the recognition and production posttests. The results highlight the efficiency of spacing techniques in teaching lexical collocations in a foreign language. The results of this study can lead language teachers to include such techniques as ESR and USR as effective methods to improve language learners’ lexical knowledge.